Barbados cherry grafting and budding under semi-shade conditions - Neto, Luiz Gonzaga; do Amaral, Marcelo Gurgel; Saueressig, Milton E. (Pesquisa Agropecuaria Brasileira, 1996)
In a work carried out at the Experimental Station of Bebedouro of the Centro de Pesquisa Agropecuária do Trópico Semi-Árido of Embrapa, in Petrolina, PE, Brazil, in 1993, Barbados cherry and budding methods were studied. In randomized blocks with split-plot design and six replications, three vegetative propagation methods (cleft grafting, patch budding, splice grafting) were used as the main treatments, whereas protection of the graft or bud by a plastic bag and no protection, were used as subtreatments. Ten plants per plot and five plants per subplot in six replications were used. Patch budding gave the best results among the propagation techniques studied, with a high success percentage (86.70%), when the bud was protected. The protection of the graft or bud by plastic bags increased consistently the success percentage for all grafting and budding methods studied.